Explaining visual shape–taste crossmodal correspondences - Spence, C (Brill Academic Publishers, 2023)
A growing body of experimental research now demonstrates that neurologically normal individuals associate different taste qualities with design features such as curvature, symmetry, orientation, texture and movement. The form of everything from the food itself through to the curvature of the plateware on which it happens to be served, and from glassware to typeface, not to mention the shapes of/on food product packaging have all been shown to influence people’s taste expectations, and, on occasion, also their taste/food experiences. Although the origins of shape–taste and other form–taste crossmodal correspondences have yet to be fully worked out, it would appear that shape qualities are occasionally elicited directly. However, more often, there may be a metaphorical attempt to translate the temporal qualities of taste sensations into a spatial analogue. At the same time, emotional mediation may sometimes also play a role in the affinity people experience between shape properties and taste. And finally, it should be acknowledged that associative learning of the relation between packaging shapes, glassware shapes, logos, labels and iconic food forms that commonly co-occur with specific taste properties (i.e., in the case of branded food products) may also play an important role in determining the nature of shape–taste correspondences. Ultimately, however, any attempt to use such shape–taste correspondences to nudge people’s behaviour/perception in the real world is made challenging due to the fact that shape properties are associated with multiple qualities, and not just taste.